2015
DOI: 10.1016/j.ifacol.2015.06.419
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the impact of short food supply chain on emigration: A study of Valencia community in Spain

Abstract: Recent financial crisis had severe impact on many economies around the globe. In Spain, it has resulted in increasing job loss, increasing short food supply chain businesses and rise in emigration. This research investigates how direct trades between producers and consumers (short supply chain) affect decisions of those who have decided to emigrate abroad. This paper also questions whether short supply chains can be part of the solution to restrict emigration by creating employment opportunities in depressed e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 15 publications
0
10
0
2
Order By: Relevance
“…Short food chain supply (SFSC) systems provide multiple benefits (of economic, social, environmental, cultural, and health nature) for people and society as a whole: new job opportunities in the agri-food sector at local level [ 54 ], encouraging knowledge transfer, counter-balancing the effects of population migration [ 55 ] or gentrification, supporting the local services and suppliers by sustaining the stores of small producers and farmers’ markets, preserving cultural heritage, including promotion of tourism [ 56 ] and local gastronomy, and improving the quality of life by securing access to healthier food [ 57 ].…”
Section: Methodsmentioning
confidence: 99%
“…Short food chain supply (SFSC) systems provide multiple benefits (of economic, social, environmental, cultural, and health nature) for people and society as a whole: new job opportunities in the agri-food sector at local level [ 54 ], encouraging knowledge transfer, counter-balancing the effects of population migration [ 55 ] or gentrification, supporting the local services and suppliers by sustaining the stores of small producers and farmers’ markets, preserving cultural heritage, including promotion of tourism [ 56 ] and local gastronomy, and improving the quality of life by securing access to healthier food [ 57 ].…”
Section: Methodsmentioning
confidence: 99%
“…In terms of economic sustainability, in optimal cases, short trade chains can support local and regional development and contribute to the consumers' food quality [9] and job creation [13,62]. Experiences from several case studies show that SSC channels are mostly used by relatively small farms [63][64][65] (or are most profitable for them).…”
Section: Economic Sustainability Of Short Supply Chainsmentioning
confidence: 99%
“…They integrate supply chain functions in this way, but they also need to connect horizontally [66]. In many cases, producers' participation in SFSC is motivated by interdependence, self-employment [13], or by selling directly to the consumer at better prices, avoiding retail and wholesale trade [67]. In this way, they can receive a higher return on the value of the products [68].…”
Section: Economic Sustainability Of Short Supply Chainsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, the social benefits of SFSCs have been extensively investigated. The most widely acknowledged social benefits of SFSCs in existing studies are identified as the improved food quality and security (Hinrichs, 2000;Marsden et al, 2000;Hinson and Bruchhaus, 2008;Smith, 2008;Jones and Bhatia, 2011;Bimbo et al, 2015;Engelseth, 2016;Leiper and Sather, 2017), additional employment opportunities (Ilbery and Maye, 2005;Sgroi et al, 2014;Falguieres et al, 2015;Tudisca et al, 2015;Mundler and Laughrea, 2016;Rover et al, 2017), and the regained consumers' trust (Hinson and Bruchhaus, 2008;O'Kane and Wijaya, 2015;Giampietri, 2016;Giampietri, 2018). Meanwhile, the friendly shopping atmosphere (Hinson and Bruchhaus, 2008;Watts et al, 2011;Zirham and Palomba, 2015;Benedek et al, 2017;Leiper and Sather, 2017) and the social connection with customers and fellow farmers (Beckie et al, 2012) are also noted as the improved social sustainability of SFSCs.…”
Section: Comparison With Existing Studiesmentioning
confidence: 99%